Evaluation of respiratory heat loss by evaporation and convection in ruminants - Nascimento, Carolina C [UNESP]; Maia, Alex S. [UNESP]; Da Silva, Roberto G.; Chiquitelli Neto, Marcos [UNESP]; Camerro, Leandro Z. [UNESP]; Costa, Cintia Carol D. [UNESP] (American Society of Agricultural and Biological Engineers (ASABE), 2016)
In order to evaluate heat losses in the respiratory tract through convection and evaporation in livestock the aim of this study was used an equations developed from the tracheal dimensions of ruminants based on the theory of turbulent flow. The study was conducted in three differents regions São Paulo State University (UNESP) in Campus is Jaboticabal, SP, Brazil, Apta Ribeirão Preto, SP, Brazil and UNESP, Campus of Ilha Solteira, SP, Brazil. Was used five Nellore beef cattle, nine Anglo Nubiana goat, 12 Jersey dairy cattle and 10 Guzerat beef cattle, with a body weight of 743.4, 61.67, 362.1 and 420 kg, respectively. The environment variables air temperature, (TA, °C), black globe temperature, (Tg, °C) and relative humidity (RH, %) were measured by Data Loggers. An indirect calorimetry system with use of facial mask adjusted to the animal's muzzle was used. The respiratory rate (RR, breaths min-1), ventilation (VE, L s-1), expired air temperature (TEXP, °C), saturation vapour pressure at expired air temperature (PEXP, kPa) were measured simultaneously, the sensible and latent heat flows was calculation according to da Silva e Maia (2013). The results showed the Jersey cows present the higher sensible and latent heat loss by respiratory tract with mean values of 2.02±0.02 and 23.7±0.009, respectively. The mean of evaporative heat loss by respiratory tract was 8.59±0.01; 9.8±0.06; 3.4±0.05 and of respiratory convection was 0.71±0.08; 0.7±0.007; 0.72±0.005 W m-2 for Guzerat, Nellore and Anglo Nubian, respectively.
Keywords: Beef cattle; Goat; Indirect calorimetry; Latent heat production